Low Temperature Growth of Single-Walled Carbon Nanotubes from Pt Catalysts under Low Ethanol Pressure by Alcohol Gas Source Method. (9th October 2012) - Kondo, Hiroki; Fukuoka, Naoya; Maruyama, Takahiro
Abstract : Growth of single-walled carbon nanotubes (SWNTs) was carried out on SiO2 /Si substrates with Pt catalysts at 400, 450, and 700°C under various ethanol pressures using an alcohol gas source method in a high vacuum, and the grown SWNTs were characterized by scanning electron microscopy (SEM) and Raman spectroscopy. Irrespective of the growth temperature, both G band and RBM peaks were observed in the Raman spectra under the optimal ethanol pressure ( 1 × 10 − 3 Pa), indicating that SWNTs grew below 450°C from Pt. At 400°C, both average diameter and diameter distribution were drastically reduced, and those were fairly smaller and narrower, compared to those for SWNTs grown with Co.